HISTOLOGICAL CHARACTERISTICS OF INTERCELLULAR COMPONENTS OF PAPILLARY DERMIS OF THE SKIN OF HEIFERS OF DIFFERENT BREEDS IN POSTNATAL ONTOGENESIS - Кириловський, С. М. (Scientific Progress & Innovations, 2013)
Papillary dermis layer of skin of heifers has a complex heterogeneous organization of intercellular substance of connective tissue and topographically divided on morphological characteristics of collagen, elastic, reticular fibers and basic substance on several levels. Growth of papillary dermis of heifers’ skin is accompanied by internal structural transformations of papillary dermis. At an early age the differences in the architectonics of collagen network on subepidermal level of papillary dermis in various breeds of heifers are clearly seen.